2005
DOI: 10.1152/ajpheart.00591.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of iNOS is associated with endothelial dysfunction and impaired pressor responsiveness in streptozotocin-induced diabetes

Abstract: (MABP) and heart rate (HR), endothelial dysfunction, and attenuated pressor responses to vasoactive agents. We investigated whether these abnormalities are due to diabetes-associated activation of inducible nitric oxide synthase (iNOS). In addition, the effect of the duration of diabetes on these abnormalities was also evaluated. Diabetes was induced by administration of 60 mg/kg STZ via the tail vein. One, 3, 9, or 12 wk after STZ injection, MABP, HR, and endothelial function were measured in conscious unres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 41 publications
10
96
0
2
Order By: Relevance
“…Recent reports reveal that decreased expression of eNOS accompanies increased expression of iNOS and nitrotyrosine during the progression of diabetes in rats [81]. This finding suggests that induction of iNOS in cardiovascular tissues is dependent on the duration of diabetes and contributes significantly to depressed responses to vasoactive agents.…”
Section: Animal Studiesmentioning
confidence: 92%
“…Recent reports reveal that decreased expression of eNOS accompanies increased expression of iNOS and nitrotyrosine during the progression of diabetes in rats [81]. This finding suggests that induction of iNOS in cardiovascular tissues is dependent on the duration of diabetes and contributes significantly to depressed responses to vasoactive agents.…”
Section: Animal Studiesmentioning
confidence: 92%
“…This hypothesis is based on the inherent capacity of iNOS to produce greater amounts of NO (in the order of nanomols to micromols) (39) and on the fact that the aorta from our diabetic animals, treated or not, presented increased intensities of immunostaining for iNOS. Therefore, despite a reduction in eNOS immunostaining in the endothelium from the aorta of diabetic rats, which was observed by other authors (40,41), the increase in iNOS immunostaining could have made sufficient NO available to exert its biological effects. These ideas were also defended by Bojunga and cols., who had similar results (42).…”
Section: Discussionmentioning
confidence: 72%
“…It was found that, apart from endothelial cells, NO from sources such as inducible NOS (iNOS) and neuronal NOS (nNOS) may contribute to increased NO in diabetes (Nagareddy et al 2005). Increased expression and activity of iNOS in superior mesenteric arteries (SMA) from 12-14 week STZ-induced diabetic rats were reported earlier (Bardell and MacLeod 2001).…”
Section: Resultsmentioning
confidence: 88%